Pendugaan Bobot Badan Kambing Saburai Menggunakan Ukuran-ukuran Tubuh dengan Metode Regresi Linear, Kuadratik, dan Eksponensial - Nugraha, Ega; Dakhlan, Akhmad; Kurniawati, Dian; Qisthon, Arif (Jurnal Riset dan Inovasi Peternakan, 2025)
This study aims to determine the relationship between body measurements and body weight of Saburai goats and to estimate body weight using linear, quadratic, and exponential regression methods. The research was conducted through a survey using purposive sampling to determine the location and select Saburai goat samples aged 1--3 years based on dental condition. The samples consisted of male and non-pregnant female goats. Body weight was measured using a scale, while body measurements were obtained through direct measurement. The collected data were tabulated and analyzed. Analysis of body measurements using linear, quadratic, and exponential regression methods was performed with the R program. The results of this study showed that the highest correlation coefficient (r) between body measurements and body weight was found in chest girth using linear, quadratic, and exponential regression, with values of 0,92 (linear), 0,92 (quadratic), and 0,91 (exponential), respectively. The regression equations between body weight and chest girth were: BB = -45,02690 + 1,07704 LD (linear), BB = -22,581345 + 0,464609 LD + 0.004129 LD² (quadratic), and BB = 3,58652 exp (0,03027 LD) (exponential). The coefficients of determination (R²) ware 84% for the linear model, 84% for the quadratic model, and 83% for the exponential model, respectively. It can be concluded that chest girth is the best predictor for estimating the body weight of Saburai goats using linear, quadratic, and exponential models.